Analysis of Protein Glycation Products by MALDI-TOF/MS - Kislinger, Thomas; Humeny, Andreas; Becker, Cord-Michael; Peich, Carlo; Pischetsrieder, Monika (Annals of the New York Academy of Sciences, 2005)
Matrix-assisted laser desorption ionization-mass spectrometry with time-of-flight detection (MALDI-TOF/MS) is a promising tool to analyze advanced glycation end product (AGE)-modified proteins. The combination of soft ionisation (MALDI) with time-of-flight mass detection allows analysis of peptides and proteins of a molecular mass up to 300 kDa with minimal sample workup. Because the direct structural analysis of intact AGE proteins is not possible due to the formation of broad and poorly resolved peaks, peptide mapping was introduced into the analysis of AGE proteins by MALDI-TOF/MS, allowing site-specific analysis of defined AGEs. When methylglyoxal-modified lysozyme was subjected to MALDI-TOF/MS peptide mapping, methylimidazolone and argpyrimidine attached to the arginine residue and carboxyethyl (CEL) bound to the lysine were detected on peptideaa1-7 (KVFGRCE). In contrast, only one methylimidazolone was found on peptideaa8-35 (LAAAMKRHGLDNYRGYSLGNWVCAAKFE) and peptideaa120-129 (VQAWIRGCRL), respectively. The analysis of AGE protein, which had been incubated with glucose, revealed the presence of am Amadori product and a carboxymethyl residue (CML) on peptideaa1-7 and peptideaa8-35, as well as an imidazolone A on peptideaa120-129. Furthermore, the early Maillard reaction of lysozyme, which had been glycated by seven different sugars, was monitored by MALDI-TOF/MS peptide mapping. Finally, this approach was successfully applied for site- and product-specific relative quantification of AGEs. For example, kinetics of CML and Amadori product formation on peptide aa1-7, as well as imidazolone A formation on peptide aa120-129, were determined. © 2005 New York Academy of Sciences.
UnivIS-Import:2015-04-16:Pub.2005.nat.dchph.llmch.analys
Keywords: Advanced glycation end products; Maillard reaction; MALDI-TOF/MS; Mass spectrometry; Peptide mapping